Prinsip-Prinsip Utama Pembelajaran: Kajian Konseptual dalam Perspektif Ilmu Pendidikan - Muhammad Saleh; Usman . (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
This study aims to examine and analyze the main principles of learning from an eucational perspective, which include the principles of demonstration, application, task-centered learning, activation, and integration, as well as their implementation in the learning process. This research employs a library research method with a descriptive qualitative approach through the exploration of various literature sources such as books, journals, and other scholarly references. Data analysis is conducted using content analysis techniques through stages of data reduction, data presentation, and conclusion drawing. The findings reveal that these five principles are closely interconnected and form a comprehensive and systematic learning framework. The demonstration principle emphasizes the importance of concrete examples in learning; the application principle directs learners to implement knowledge in real-life contexts; the task-centered principle focuses on problem-based learning activities; the activation principle functions to elicit learners’ prior knowledge; and the integration principle connects various learning concepts to everyday life. The implementation of these principles aligns with Merrill’s First Principles of Instruction, which highlight the stages of activation, demonstration, application, and integration in effective learning. Therefore, the application of these principles can enhance the effectiveness, meaningfulness, and overall quality of student-centered learning.